Biological Function of Medium-Chain Fatty Acids and Their Application in Aquatic Animals: A Review - Haiyan Liu; Wenzong Zhou; Chenggang Cai; Fengqin Feng; Haiying Cai; Hang Yang (Animals)
Medium-chain fatty acid triglycerides (MCTs) possess antibacterial, antiviral, nutritional, and other biological activities and have demonstrated significant application potential in humans and terrestrial animals. In recent years, with the development of the green aquaculture industry, MCTs have been gradually applied to aquaculture animals, which can enhance growth performance, improve flesh quality, regulate lipid metabolism, boost immune activity, and modulate the intestinal flora, thereby improving the production efficiency of aquaculture. This paper elaborates in detail on the biological activities of MCTs and their applications in aquatic animals, providing a theoretical and practical basis for the application of MCTs in aquaculture.